Global research trends in green advertising and green purchase intention: A decade of bibliometric insights - Zinulaen; Dananjoyo, Radyan (Jurnal Siasat Bisnis, 2026)
Purpose – This study maps the development of research on green advertising and green purchase intention from 2015 to 2025. This study is motivated by the increasing relevance of environmental sustainability issues in marketing practices and consumer behavior.Design/methodology/approach – This study uses a bibliometric approach by analyzing 150 scientific articles indexed in Scopus using the VOSviewer software. The analysis was conducted through four stages: initial search, screening, examination of bibliographic attributes, and thorough bibliometric analysis with a focus on keyword linkage networks, author collaboration, and citations.Findings – The results of the study show a significant increase in the number of publications regarding green advertising and green purchase intention. Five thematic clusters were successfully identified: consumer perception of green messages, psychological attitudes towards the environment, macro sustainability issues, ethical challenges such as greenwashing, and communication effectiveness. The United States, India, and China are major contributors to the publication, although collaboration between authors is still limited.Research limitations/implications – This study was limited to English-language journal articles indexed in Scopus, so it did not include conference proceedings or publications in other languages. Further research is recommended to explore the effectiveness of green advertising on specific products (e.g. sustainable fashion), the role of social media in green campaigns, as well as using experimental methods to test causal relationships.Practical implications – The findings of this study can be leveraged by marketing practitioners to design more effective green advertising by aligning messages with consumer values and trust. The study also emphasizes the importance of honesty in communication so as not to cause skepticism about greenwashing practicesOriginality/value – This study is the first systematic bibliometric mapping of green advertising and green purchase intention using VOSviewer, which reveals key trends, influential authors, and research gaps that can be leveraged for further study and development of sustainable marketing strategies.